Optimal price setting during a currency changeover: theory and evidence from french restaurants - Berardi, Nicoletta; Eife, Thomas A.; Gautier, Erwan (Applied economics, 2014)
This article studies firms’ price-setting decision during a currency changeover. Buyers’ difficulties with the new nominal price level may create incentives to raise prices temporarily but doing so comes at the risk of damaging a seller’s standing as a fair retailer. We model firms’ trade-off and study conditions under which increasing or decreasing prices is optimal. A difference-in-differences analysis based on micro-data of French restaurants strongly supports the model’s predictions. Prices during the 2002 changeover in the European Monetary Union were less likely to rise in larger restaurants, nontourist restaurants and when prices were advertised.